(untitled) (Indian Journal of Child Health, 2024)
Background: Neonatal jaundice is a very common condition worldwide, occurring in up to 60% of term and 80% of pre-term newborns in the 1st week of life and the most common cause for readmission. The present study was conducted to evaluate the predictive value of umbilical cord blood albumin level for subsequent development of neonatal jaundice in healthy term neonates. The present study is conducted to find usefulness of cord blood albumin in predicting the subsequent development of significant neonatal jaundice. Methods and Methods: This is a hospital-based prospective study conducted in 100 healthy term neonates. Cord blood albumin level estimation was done at birth. Total serum bilirubin estimation was done for all babies with clinically suspected jaundice at 72–96 h of age. The neonates were divided into three Groups A, B, and C based on the cord albumin levels of <2.8 g/dL, 2.8–3.3 g/dL, and >3.3 g/dL, respectively. The main outcome of the study was inferred in terms of serum bilirubin ≥17 mg/dL, newborn required phototherapy, and exchange transfusion. Results: Groups A, B, and C had 21, 35, and 44 newborns, respectively. In Group A, 18 (85.7%) neonates had total bilirubin of >17 mg/dL, of which 16 (76.19%) required phototherapy and 2 (9.52%) needed exchange transfusion. 23 (65.7%) neonates in Group B developed jaundice, of which 12 (34.2%) needed phototherapy and none of them required exchange transfusion. In Group C, 15 (34.09%) developed jaundice of which 1 (2.2%) required phototherapy and none of them required exchange transfusion (p<0.001). Conclusion: Cord blood albumin level ≤2.8 g/dL is a significant risk factor for developing neonatal hyperbilirubinemia that requires early intervention, while cord blood albumin >3.3 g/dL is probably safe for early discharge. Hence, this can help to identify the at-risk neonates. Hence, routine determination of cord blood albumin level can be advocated to keep a track on at-risk neonates.